Evaluation of Lime-Treated Lateritic Soil for Reservoir Shoreline Stabilization - Ricardo Moreira Vilhena (Water, 2020)
Sedimentation is one of the major problems addressed by reservoir management, and requires extensive effort to control it. This paper aims to evaluate the efficiency of the soil–lime stabilization technique for reservoir shores. The treatment consisted of spraying hydrated lime in slurry form over the surface of a lateritic clay sample with 1, 2, and 4% lime solution and curing times of 1, 7, 28, and 56 days with air-drying and moist-room storage. In addition, a single test with less than 1% lime solution by weight percentage was carried out. The post-cured specimens were mapped with SEM and X-ray analyses. A wave flume test was performed in samples subjected to diverse conditions of lime content, type, and curing time. The results showed that the present technique produces a Ca-rich crust by carbonation rather than stabilizing it and that the lime content and type of curing generate improvements in soil loss reduction, but the curing time does not. The technique gave relative protection against water level variation and wave impacts, but it is necessary to consider a frequent application of lime on the lateritic soil.